Scandium fluorides - Melnikov, P. [UNESP]; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP] (Elsevier, 1997)
A new modification of scandium fluoride has been synthesised. The compound is deficient in fluorine, with the composition ScF2.76. It belongs to the tetragonal system, lattice parameters being a = 3.792 and c = 6.740 Å and may be obtained at low temperatures by the decomposition of the precursor NH4ScF4. The reaction is topotactic, tetragonal parameters of the precursor are a = 4.021 and c = 6.744 Å. Structural relationships with various fluorides and ammonium aminofluorides are discussed. This synthesis route with IR-assisted decomposition should be considered as a soft-chemistry approach. © 1997 Elsevier Science S.A.
Keywords: Fiber glasses; Fluorides; Scandium; Ammonium compounds; Crystal structure; Decomposition; Fluorine; Lattice constants; Modification; Synthesis (chemical); Ammonium aminofluoride; Scandium fluoride; Scandium compounds